2020
DOI: 10.1097/wno.0000000000000829
|View full text |Cite
|
Sign up to set email alerts
|

A Reliability and Comparative Analysis of the New Randomized King-Devick Test

Abstract: Objective: The King-Devick (K-D) test is a rapid visual screening tool that can assess underlying brain trauma such as concussion via impairments in saccadic rhythm. A new tablet version of the K-D test using randomized numbers is now available, but reliability for this new version and comparison to the traditional K-D test has not yet been reported. Known for learning effects in the test, the aim of this study was to determine test–retest reliability and to compare performance of the new “randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This learning-effect problem also affects the King Devick test because it is very similar. 64 The repeatability and agreement of the KD test show the same general behavior. Correlations (ICC) were high, but there is a significant improvement in performance in the second administration (reduced time of execution).…”
Section: Repeatabilitymentioning
confidence: 64%
“…This learning-effect problem also affects the King Devick test because it is very similar. 64 The repeatability and agreement of the KD test show the same general behavior. Correlations (ICC) were high, but there is a significant improvement in performance in the second administration (reduced time of execution).…”
Section: Repeatabilitymentioning
confidence: 64%
“…The reliability of the EyeGuide was comparable to other eye movement cognitive tests (e.g., King–Devick). For example, studies in adolescent populations have reported moderate to good ICCs of 0.81 (95%CI: 0.73, 0.87) and 0.91 (95%CI: 0.86, 0.95) [ 32 , 33 ] and in adults, good ICCs of 0.95 (95% CI: 0.91, 0.97) and 0.91 (95%CI: 0.80, 0.96) [ 28 , 34 ]. The data in the present study are also consistent with previously published EyeGuide data.…”
Section: Discussionmentioning
confidence: 99%
“…Participants undertook testing in a quiet room, away from potential distractions. Participants were also allowed usual eyewear such as prescription contact lenses or glasses, following standard protocol from other eye-movement testing such as the King–Devick [ 28 ] as well as recommended protocol from EyeGuide. Each participant completed three trials with a 30 s rest between each trial to avoid potential fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, participants were recruited if they lacked a history of concussion and met all the exclusion and inclusion criteria. Furthermore, participants had a KD score of 40 ± 6.3, which is within the normal range of this demographic [ 59 , 60 , 61 ] to ensure sample homogeneity.…”
Section: Discussionmentioning
confidence: 99%